Penerapan Model Discovery Learning untuk Meningkatkan Hasil Belajar Kognitif Siswa pada Pembelajaran Penddikan PKn - Eva Indah Lestari; Abdul Wahidin; Abdul Sakban; Sitti Ramlah; Zumri Zumri (Muhammadiyah University of Mataram, 2023)
Rendahnya hasil belajar kognitif siswa disebabkan oleh Kesulitan dalam memahami pembelajaran PPKn di Kelas. Dapat dilihat dari hasil ulangan harian siswa mata pelajaran PPKn kelas X IPS 4 di bawah KKM dan Nilai rata-rata siswa kelas X IPS 4 yaitu 50,4 yang merupakan nilai yang jauh dari KKM yang telah ditetapkan yaitu 75. Penelitian ini bertujuan untuk meningkatkan hasil belajar PPKn siswa kelas X IPS 4 SMA Negeri 3 Mataram melalui penerapan pembelajaran Discocery Learning. Penelitian ini berbentuk penelitian tindakan kelas yang dilakukan selama dua siklus. Hasil penelitian menunjukkan bahwa Hasil belajar kognitif siswa mengalami peningkatan atau mencapai KKM di atas rata- rata 97.2. The low cognitive learning outcomes of students in Civic Education (PPKn) are caused by difficulties comprehending the classroom material. The results can be seen from the Civic Education (PPKn) daily tests for class X IPS 4 students under the Minimum Criteria of Mastery Learning (KKM) as well as the average value of class X IPS 4 students is 50.4 means a distant value from the Minimum Criteria of Mastery Learning (KKM) 75 that has been set. This study aims to improve the student's learning outcomes of Civic Education (PPKn) in class X IPS 4 SMA Negeri 3 Mataram, through the application of Discovery Learning learning. The research form is classroom action research conducted for two cycles. The results showed that the student's cognitive learning outcomes had increased or achieved the Minimum Criteria of Mastery Learning (KKM) above the average value of 97.2